IMPLEMENTASI METODE PEMBELAJARAN OUTDOOR BERBASIS PROYEK UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA MATA PELAJARAN GEOGRAFI FASE F DI SMAN 16 PADANG - Fina Fitria; Loli Setria; Ade Irma Suryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the ongoing problem of low motivation to learn Geography. Conventional learning methods, which tend to be teacher-centered and watchful, can quickly lead to student boredom and inactivity. The purpose of this study was to identify and analyze data showing differences in the application of outdoor learning methods in improving Geography learning motivation among students at SMAN 16 Padang. The research used purposive sampling. The population consisted of classes XI.F4, XI.F5, XI.F6, and XI.F9, as these are the only classes interested in Geography. The sampling was based on daily test scores (PH) for two classes. The instruments used in this study were questionnaire validity and reliability tests, and data analysis techniques included descriptive analysis, normality tests, homogeneity tests, and hypothesis testing. The results of the study on Geography Learning Motivation of Students at SMAN 16 Padang, based on descriptive analysis, showed that the experimental class (Outdoor Learning) obtained a score of 92%, categorized as Very High, while the control class (Conventional) obtained a score of 88%, categorized as Very High. Based on the independent sample t-test on student questionnaire responses, it can be concluded that the sig value of 0.044 < 0.05 indicates that this coefficient value is significant because the calculated t-value > t-table value = 2.053 > 0.339. Thus, it can be interpreted that Ho is rejected and Ha is accepted. Therefore, there is a difference in the effect of outdoor learning methods on student learning motivation in Geography at SMAN 16 Padang.